ALS risk factors: Industrial airborne chemical releases. (15th February 2022) - Andrew, Angeline; Zhou, Jie; Gui, Jiang; Shi, Xun; Li, Meifang; Harrison, Antoinette; Guetti, Bart; Nathan, Ramaa; Butt, Tanya; Peipert, Daniel; Tischbein, Maeve; Pioro, Erik P.; et al.
Abstract: Most amyotrophic lateral sclerosis (ALS) cases are sporadic (∼90%) and environmental exposures are implicated in their etiology. Large industrial facilities are permitted the airborne release of certain chemicals with hazardous properties and report the amounts to the US Environmental Protection Agency (EPA) as part of its Toxics Release Inventory (TRI) monitoring program. The objective of this project was to identify industrial chemicals released into the air that may be associated with ALS etiology. We geospatially estimated residential exposure to contaminants using a de-identified medical claims database, the SYMPHONY Integrated Dataverse®, with ∼26, 000 nationally distributed ALS patients, and non-ALS controls matched for age and gender. We mapped TRI data on industrial releases of 523 airborne contaminants to estimate local residential exposure and used a dynamic categorization algorithm to solve the problem of zero-inflation in the dataset. In an independent validation study, we used residential histories to estimate exposure in each year prior to diagnosis. Air releases with positive associations in both the SYMPHONY analysis and the spatio-temporal validation study included styrene (false discovery rate (FDR) 5.4e-5), chromium (FDR 2.4e-4), nickel (FDR 1.6e-3), and dichloromethane (FDR 4.8e-4). Using a large de-identified healthcare claims dataset, we identified geospatial environmental contaminants associated with ALS. The analytic pipeline used may be applied to other diseases and identify novel targets for exposure mitigation. Our results support the future evaluation of these environmental chemicals as potential etiologic contributors to sporadic ALS risk. Graphical abstract: Image 1 Highlights: The Toxics Release Inventory (TRI) monitors airborne industrial chemical releases. Our spatio-temporal approach used a validation study with residential histories. ALS risk factors: nitric acid, styrene, chromium, nickel, and dichloromethane.